Efektivitas Kegiatan Edukasi Pernikahan Dini dan Tablet Tambah Darah pada Siswa MTSn Al-Wafa SumberjambeEfektivitas Kegiatan Edukasi Pernikahan Dini dan Tablet Tambah Darah pada Siswa MTSn Al-Wafa Sumberjambe - Dewi Rokhmah; Evi Riski Permatasari; Anita Dewi Prahastuti Sujoso; Rista Dwi Hermilasari (Pendidikan Fisika FKIP UNEJ, 2022)
The main health problem in Sumberjambe is stunting. It is known from the prevalence of toddlers who experience stunting of 80.8% which is caused by one of the stunting factors, namely early marriage. Sumberjambe Village has a fairly high number of early marriages. As many as 40% of couples of childbearing age are too young with marriages that are too early and have the potential to increase the incidence of LBW (Low Birth Weight) so that health programs are needed such as P2GBS (Prevention and Eradication of a Stunting Free Generation) which includes educational activities regarding early marriage and giving blood tablet. This study aims to analyze the effectiveness of early marriage education activities and giving blood tablets. The activity was carried out using the socialization and discussion method with the target students of MTs Al-Wafa Sumberjambe using poster media, educational videos, early marriage modules and blood-adding tablets, power points, early marriage tote bags, and pre-test and post-test sheets. The results of this study from the activities carried out showed that there was an increase in target understanding in early marriage education by 9.42% with a pre-test result of 32.83% and a post-test of 42.25% where the activity had an effectiveness result of >1 so that the activity was effectively carried out to help reduce the prevalence of stunting in Sumberjambe Village.